PENGARUH PELATIHAN PASAR MODAL PADA MINAT BERINVESTASI MAHASISWA AKUNTANSI UNIVERSITAS MUHAMMADIYAH MAKASSAR - Usman, Nur Alfriani; Rahma, Besse; Syaifudin, Akhmad Mufly; Muchran, Muchriana (IJMA (Indonesian Journal of Management and Accounting), 2024)
The aim of this research is to determine the influence of the capital market on investor interest. The research was conducted at the Faculty of Economics and Business, Muhammadiyah University of Makassar on Bachelor of Accounting students using the multiple linear regression analysis method. This research determination uses the Slovin formula from a known population as a sample. From the calculation results, a sample of 75 active student respondents from the class of 2021 was obtained. The type of survey used was a quantitative survey which was formed using numbers through a questionnaire whose measurement used a Likert scale. The research results show that capital market training has a good and significant influence on investor interest.